Mendakwahkan Al-Qur’an di Era Media Sosial: Telaah Terhadap Program Every Day Mutiara Al-Qur’an - Tsaabit Alal Haq; Sunaryanto (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2024)
This study aims to analyze the Every Day Muatiara Al-Qur'an Program using SWOT analysis. The research method used is a qualitative approach. Data collection methods with interviews, documentation, and observation. The results of the study are the Every Day Mutiara Al-Qur'an program that the meaning of every is interpreted that every day, the hope is that no day is missed without contemplating the Qur'an. The meaning of pearl is in accordance with the name of the jewelry that everyone likes. The hope is that every member will get worldly and afterlife jewelry by contemplating the Qur'an. The Qur'an is the Book of Allah that should receive great attention in life. The use of the name EMQ is an abbreviation that is easy to remember and full of meaning. So that everyone is happy with the beauty of the meaning of the Qur'an by contemplating it. With the EMQ Program via WhatsApp, there is a hope that all members will get pearls from the Qur'an that are more beautiful than pearls in the form of worldly jewelry because the Qur'an is worldly jewelry and the afterlife jewelry. The EMQ program using WhatsApp has not been effective because each member only submits the results of their tabbur through the WhatsApp group. This program needs to build a new management model using social media so that the EMG program can be effectively implemented by members.